A study of the genetic diversity in the world soybean collection using microsatellite markers associated with fungal disease resistance - A. K. Zatybekov; Y. T. Turuspekov; B. N. Doszhanova; S. I. Abugalieva (Труды по прикладной ботанике, генетике и селекции)
Background. Soybean (Glycine max (L.) Merr.) gradually becomes one of the leading legume crops in Kazakhstan. The area under soybeans in the country has been increasing annually and requires the development of adapted cultivars with a higher yield, improved quality characters, and resistance to emerging fungal diseases. The enlargement of the crop’s gene pool also suggests the need to study and document local soybean accessions to meet the standards of the available world soybean collection by using reliable and informative types of DNA markers.Materials and methods. In this study, the soybean collection consisting of 288 accessions from different countries, including 36 cultivars and promising lines from Kazakhstan, was studied. The molecular genetic analysis was performed using nine polymorphic SSR (simple sequence repeats) markers, seven of which (Satt244, Satt565, Satt038, Satt309, Satt371, Satt570 and Sat_308) were associated with resistance to three main fungal diseases of soybean – frogeye leaf spot, fusarium root rot, and purple seed stain.Results. The average PIC (polymorphism information content) value of the analyzed SSR markers constituted 0.66 ± 0.07, confirming their highlevel polymorphism. The principal coordinate analysis suggested that the local accessions were genetically most close to the accessions from East Asia. As the collection showed a robust resistance to three studied fungal diseases in Almaty Region during 2018–2019, the distribution of the studied SSR markers in the population was not significantly associated with resistance to the analyzed diseases under field conditions.Conclusion. SSR genotyping of the soybean collection helped to identify accessions that potentially possess resistance-associated alleles of fungal disease resistance genes. The data obtained can be further used for the development of DNA documentation and the breeding the promising cultivars and lines of soybean.